2017
DOI: 10.1159/000475526
|View full text |Cite
|
Sign up to set email alerts
|

ENETS Consensus Guidelines for the Standards of Care in Neuroendocrine Neoplasms: Peptide Receptor Radionuclide Therapy with Radiolabelled Somatostatin Analogues

Abstract: The purpose of these guidelines is to assist physicians caring for patients with neuroendocrine neoplasia in considering eligibility criteria for peptide receptor radionuclide therapy (PRRT) and in defining the minimum requirements for PRRT. It is not these guidelines' aim to give recommendations on the use of specific radiolabelled somatostatin analogues for PRRT as different analogues are being used, and their availability is governed by varying international regulations. However, a recent randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
241
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(248 citation statements)
references
References 82 publications
2
241
1
4
Order By: Relevance
“…In the present study, we focused on subjects only suffering from NET of pancreatic origin. For NET, treatment options have improved in the last years [35]: The NETTER-1 trial revealed impressive findings using PRRT in midgut NET [8]. Moreover, recent developments of systemic agents such as everolimus or axitinib have also demonstrated favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on subjects only suffering from NET of pancreatic origin. For NET, treatment options have improved in the last years [35]: The NETTER-1 trial revealed impressive findings using PRRT in midgut NET [8]. Moreover, recent developments of systemic agents such as everolimus or axitinib have also demonstrated favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 21 patients with pretreatment carcinoid syndrome, 90% benefited from therapy. The potential exacerbation of hormonal syndromes leading to crisis after PRRT must be acknowledged, and patients must be carefully selected, prepared, and monitored when treating patients with carcinoid syndrome with this modality [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Through this trial, 177 Lu-DOTA-octreotate will probably be the first widely approved agent for PRRT. The ENETS Standard of Care for PRRT clearly describes evidence, treatment protocols, and patient selection for treatment with PRRT [64]. …”
Section: Systemic Therapymentioning
confidence: 99%